SP6.1.11 ; The Effect of the Enhanced Recovery Programme for Liver Surgery on Long Term Survival - Arujunan, Kalaiyarasi; Shugaba, Abdulwarith; Uwadiae, Harmony; Lambert, Joel; Sgourakis, Georgios; Subar, Daren (British journal of surgery, 2021)
Aims The Enhanced Recovery Programme for Liver Surgery (ERPLS) has been shown to promote functional recovery and reduce hospital stay. However, its effect on long term survival has yet to be established. The aim of this study was to determine the effect of the ERPLS on 5-year patient survival. Methods This was a retrospective study of patients who underwent liver resection for colorectal liver metastasis (CRLM) between January 2011 and December 2016 at a regional hepatobiliary centre. The cohort comprised of 60 pre-ERPLS and 60 post-ERPLS patients. The primary outcome was 5-year patient survival. The secondary outcomes were length of stay (LOS), postoperative complications and 90-day readmission rates. Multivariate analysis was performed to identify independent predictors of overall survival. Results There was no significant difference in the age (p = 0.960), gender (p = 0.332) and type of resection (p = 0.198) between both groups. ERPLS was not an independent predictor for overall survival (Gehan Wilcoxon Test, p = 0.828). There was no significant difference in the LOS (p = 0.874) and 90-day readmission rates (p = 0.349). Major postoperative complications (>3a Clavien-Dindo classification) were significantly less in the ERPLS group (p = 0.02). On multivariate analysis, positive resection margins and major postoperative complications were independent predictors for overall survival. Conclusions ERPLS does not seem to have an effect on long term patient survival. However, it appears to reduce the rate of major postoperative complications. LOS and 90-day readmission rates were not influenced by ERPLS.